The Universities Ranking World Cup: a global view by continent and country from the computer science perspective - Sobral, Sónia Rolland (2020)
University rankings are lists of universities ranked according to different criteria: different systems, published annually. This article uses seven of the world's best-known global rankings and only in the context of computer science: Shanghai Ranking’s Academic, CWTS Leiden, Quacquarelli Symonds, Times Higher Education, National Taiwan University, Best Global Universities USNews and University Ranking by Academic Performance. We present the top10 universities by each ranking system and by continent and country those that appear in the top20, top100 and top500. Each of these rankings has different items and weights, which will be listed and analysed in this article. The results are very different from each other because they follow different systems. This article shows that in top10 there is a direct relationship between the massive presence of top Asian universities and the total dependence on Web of Science publications. The same is not true when the data source is Scopus database.